The Influence of Sharia Fintech Equity Crowdfunding on Business Actors: Diverse Avenues for Obtaining Finance - Nurlina, Nurlina (CV. Bimbingan Belajar Assyfa, 2024)
This research highlights the significant impact of Sharia-compliant fintech equity crowdfunding on business actors, focusing on the diverse avenues it offers for obtaining finance. The study is an empirical research aimed at understanding how Sharia fintech equity crowdfunding can serve as an alternative financing mechanism for entrepreneurs and small to medium-sized enterprises (SMEs). Through a comprehensive evaluation, the study examines the experiences and outcomes of business actors who have utilized this financing method. The research employs a systematic literature review (SLR) methodology, with specific criteria for participant selection. The subjects of the study include entrepreneurs and SMEs from various sectors and regions, totaling 150 participants. These participants were surveyed and interviewed to gather qualitative and quantitative data on their experiences with Sharia fintech equity crowdfunding. The study reveals that while Sharia fintech equity crowdfunding provides an innovative and ethical financing option, there are notable gaps in awareness and understanding among business actors. These gaps include a lack of knowledge about the processes and benefits of Sharia-compliant financing, and limited access to such platforms in certain regions. The research suggests the need for increased educational efforts and broader platform accessibility to maximize the potential of Sharia fintech equity crowdfunding. Additionally, the study uncovers a significant increase in financial inclusion and business growth among participants who effectively utilized this financing method, demonstrating its positive impact on economic development.